Pengaruh Gender dan Pemahaman Tri Pantangan terhadap Persepsi Mahasiswa mengenai Penggelapan Pajak - Wardani, Dewi Kusuma; Santoso, Galih Rohmad (Eksos, 2023)
This study aims to examine the effect of gender and understanding of tri pantangan on students’ perceptions of tax evasion. The sample used in this study were accounting and management students at the Faculty of Economics, Sarjanawiyata Tamansiswa University from 2019 to 2022 using a convenience sampling technique. This research was conducted using a sample of 122 respondents. After the respondent fills in the questionnaire, the data will be processed presented in the form of a Likert scale. The method used in this research is descriptive quantitastive using primary data. The results of this study are that gender has no effect on student perceptions of tax evasion and understanding of tri pantangan has a negative effect on student perceptions of tax evasion.